The role of nature experiences in deep ecological beliefs - Sison, Oscar D, Jr. (Animo Repository, 2020)
Deep ecology offers a philosophical outlook on the environment that emphasizes the awareness and appreciation of a holistic metaphysical understanding of nature which serves as a ground for the development of a coherent ethical system. This metaphysical holism implies an axiological arm of deep ecology that is biocentric egalitarianism, which is the belief in the inherent value of all living things. What is remarkable here is the importance that deep ecology places on certain kinds of experiences as a means to achieving this holistic outlook. This paper aims to: 1) investigate the characteristics of this class of experiences, which I hereby label as nature experience, 2) provide a framework that could explain the interaction between nature experience and fundamental deep ecological beliefs through Hume’s theory of motivation, and 3) using the methods of Experimental Philosophy, empirically test the correlation between nature experience and the presence of deep ecological beliefs as a corroboration of deep ecology’s claim. The result of the study reveals a significant positive relationship between nature experience and the presence of deep ecological beliefs. This provides a measure of support for deep ecology but more importantly, it can serve as a basis for the utilization of nature experiences in environmental programs.